Antimicrobial resistance and molecular characterization of Klebsiella species causing bovine mastitis in Nghe An province, Vietnam - Tran, My Trung; Vu, Duc Minh; Vu, Manh Duy; Bui, My Thi Phuong; Dang, Binh Xuan; Dang, Lan Thi Mai; Le, Thien Van (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: This study aimed to determine the antibiotic-resistant profile and to identify molecular characterization of some virulence genes of Klebsiella spp. isolated from mastitis samples in Vietnam. Materials and Method: A total of 468 samples from clinical mastitis cases were collected and submitted to the Laboratory. All samples were cultured, and Klebsiella spp. wasidentified through biochemical reactions and confirmed by Polymerase chain reaction (PCR). Antimicrobial resistance was tested by disk diffusion method, and virulence and resistance genes were tested by PCR. Results: An antibiogram study showed that a high proportion of isolates are multidrug-resistant (94%). All isolates were resistantto lincomycin and sulfamethoxazole, followed by ampicillin (94%), sulphonamide (66%), amoxicillin (56%), streptomycin (52%), polymyxin B (28%), colistin sulfate (12%), tetracycline (6%), ciprofloxacin (4%), florfenicol (4%), enrofloxacin (4%), piperacillin (2%), trimethoprim (2%), nalidixic acid (2%), imipenem (2%), and sulfamethoxazole/trimethoprim (2%). In contrast, all isolates showed sensitivity to gentamicin and ceftiofur. The appearance of an efflux pump system, extended-spectrum beta-lactamase (ESBL), tetracycline, and sulphonamides-resistant genes was reconfirmed using different specific primers. Capsular serotype K1 and virulence genes magA, fimH, and entB, responsible for hypermucoviscosity production, adherence, and enterobactin production, were confirmed in isolates. Multidrug resistance and virulence potential in Klebsiella spp. are changing this mastitis pathogen into a superbug and making its management harder. Conclusions: Klebsiella spp. associated with bovine mastitis in Nghe An province were mostly multidrug-resistant and carried virulence genes including fimH, entB, and antimicrobials resistant genes (blaSHV, acrAKp, tetA, etc.), but these isolates were not ESBL producers. J. Adv. Vet. Anim. Res., 10(1): 132–143, March 2023 http://doi.org/10.5455/javar.2023.j662